Condyloma Accuminatum - Ratnasari, Diana Tri (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Condyloma aaccuminatum (CA) or known as genital warts or chicken cockroach disease is a genital infections caused by human papilloma virus (HPV). In Indonesia, the incidence of CA continues to increase and is the third largest disease of sexually transmitted infections. The possibility of sexually transmitted infections with HPV-infected partners either in subclinical form is 75%. Genital HPV infection is commonly associated with moist mucosa. Microscopic abration and reccurent traumatic can increase infectivity and viral replication. HPV incubation period is between 8 weeks and 9 months. Generally does not cause a complaint but its form can cause psychological stress. Clinical features of CA is quite typical, there are 3 forms of clinical form of acuminata, keratosis, and papules. The latent period may last several months to years. Diagnosis is generally enforced simply by looking at the clinical picture. Investigations are performed if the lesions are not typical or suspicious of malignancy. A 5% acetic acid test can be used to look at subclinical trains. Histopathology is required when suspicious of malignancy. Pearly papule peniles are normal variants that have a similar picture to CA and do not need to be treated. Management of railways can be done with 25% tincture of podophylline 25%, TCA 80% -90%, imiquimod 5%, surgical excision, electrical surgery, and frozen surgery that provides satisfactory success. Therapy for pregnant women most secure by using TCA 80% -90%.Â Â